Pemahaman konseptual integrasi ilmu dan agama pada civitas academica Politeknik ‘Aisyiyah Pontianak - Nurbiah, Nurbiah; Hermanto, Hermanto (Ta'dibuna: Jurnal Pendidikan Islam, 2022)
The conceptual understanding of the integration of science and religion is very important to be implemented within Muhammadiyah educational institutions to ensure that there is no dichotomy between science and religion. The aim of this study was to analyze the conceptual understanding of the integration of science and religion among the academic community at the 'Aisyiyah Pontianak Polytechnic. The research conducted was survey research with a descriptive research design. The results of the data analysis show that the Polita Lecturer already has thoughts that understand that science and religion are an integrated unit and have applied them in the learning process. Polita students still have an understanding of the dichotomy between science and religion in a number of ways, although statements supporting the integration of science and religion are far more dominant than statements supporting the understanding of the dichotomy of science and religion. In general, the Polita academic community already has an understanding that is in line with the integration of science and religion. Abstrak Pemahaman konseptual integrasi ilmu dan agama sangat penting diterapkan di lingkungan lembaga pendidikan Muhammadiyah untuk memastikan tidak adanya paradigma dikotomi ilmu dan agama. Penelitian bertujuan untuk menganalisis pemahaman konseptual integrasi ilmu dan agama civitas academica Politeknik ‘Aisyiyah (Polita) Pontianak. Penelitian yang dilakukan merupakan penelitian survei dengan desain penelitian deskriptif. Hasil analisis data menunjukkan bahwa Dosen Polita telah memiliki pemikiran yang memahami bahwa ilmu dan agama merupakan satu kesatuan yang terintegrasi dan telah menerapkannya dalam proses pembelajaran. Mahasiswa Polita masih memiliki pemahaman dikotomi antara ilmu dan agama dalam beberapa hal walaupun pernyataan-pernyataan yang mendukung integrasi ilmu dan agama masih jauh lebih dominan dibandingkan pernyataan yang mendukung pemahaman dikotomi ilmu dan agama. Secara umum civitas academica Polita telah memiliki pemahaman yang sejalan dengan integrasi ilmu dan agama.